2023
DOI: 10.1017/jog.2022.123
|View full text |Cite
|
Sign up to set email alerts
|

Applying a distributed mass-balance model to identify uncertainties in glaciological mass balance on Brewster Glacier, New Zealand

Abstract: A distributed mass-balance model is used over a 10-year period for the re-analysis of a glaciological mass-balance time series obtained from Brewster Glacier, New Zealand. Mass-balance modelling reveals glaciological mass balance has been overestimated, with an average mass loss of −516 mm w.e. a−1 not captured by observations at the end of the ablation season, which represents 35% of the annual mass balance. While the average length of the accumulation season (199 days) remains longer than the ablation season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In our case, βf is a variable calibration parameter that can be used to reduce high melt rates. It has been reported that refreezing of melt water in glaciers or ice sheets can have a considerable contribution (Abrahim et al, 2023; Bonekamp et al, 2019; Munro, 2005).…”
Section: Swat‐glmentioning
confidence: 99%
“…In our case, βf is a variable calibration parameter that can be used to reduce high melt rates. It has been reported that refreezing of melt water in glaciers or ice sheets can have a considerable contribution (Abrahim et al, 2023; Bonekamp et al, 2019; Munro, 2005).…”
Section: Swat‐glmentioning
confidence: 99%
“…Several studies showed that redistribution of snow is essential to understand the spatial structure of local snow accumulation on timescales ranging from single events to entire seasons (Bernhardt et al., 2012; Musselman et al., 2015; J. W. Pomeroy & Gray, 1995; J. W. Pomeroy et al., 1998; Schirmer et al., 2011; Vionnet et al., 2021). Different studies implied that their calculations of glacier mass balance can be improved by accounting for drifting snow processes in the simulations (Abrahim et al., 2023; Mortezapour et al., 2020; Pradhananga & Pomeroy, 2022; Temme et al., 2023; Terleth et al., 2023). The importance of drifting snow sublimation was found to be highly variable depending on the environment and the flow conditions (e.g., Groot Zwaaftink et al., 2011; Groot Zwaaftink et al., 2013; Le Toumelin et al., 2021; Lenaerts & Van den Broeke, 2012; Lenaerts et al., 2010; MacDonald et al., 2010; Sauter et al., 2013; Strasser et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that redistribution of snow is essential to understand the spatial structure of local snow accumulation on timescales ranging from single events to entire seasons Vionnet et al, 2021). Different authors implied that their calculations of glacier mass balance might be improved by accounting for drifting snow processes in the simulations (Abrahim et al, 2023;. The importance of drifting snow sublimation was found to be highly variable depending on the environment and the flow conditions (e.g., Groot Zwaaftink et al, 2011.…”
Section: Introductionmentioning
confidence: 99%